دور حاضر میں جھوٹ کی مروجہ صورتیں اور قرآن و سنت کی روشنی میں ان کا تدارک (Al-Qamar, 2022)
Islam is a complete code of life. Islam has completely guided humanity in both worldly and religious affairs. All the principles of life have been defined in the Quran and Hadith; therefore, it has been allowed to do those things that lead to the welfare and success of the human being and the society, and it has been forbidden to do those things that cause destruction in the society and mischief arises. One of these things is lying. Lying is not only prohibited in the Qur'an and Hadith. Rather, the bad effects of lies on human society have also been described, how much loss is caused to the person himself and then to other human beings due to one lie. But despite this, many Muslims commit lies on such occasions, which they do not consider to be sins, so how can such acts lead to repentance. Therefore, in this paper, these cases of telling lies which have become common in the society nowadays are described so that a Muslim can save himself from these sins.
Keywords: Prevalent forms; Lying; Present Age; Quran and Sunnah; Solution